THE INFLUENCE OF CONTENT MARKETING AND INFLUENCER MARKETING ON PURCHASE DECISIONS FOR KENANGAN COFFEE IN MEDAN CITY WITH CONTENT CREATION AS AN INTERVENING VARIABLE - Charles Landy; Demak Claudia Yosephine Simanjuntak; Jefferson Kangra; Sugiharto; Hengki Mangiring Parulian Simarmata (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the effect of content marketing and influencer marketing on purchasing decisions of Kopi Kenangan in Medan City, with content creation as an intervening variable. This research uses a quantitative approach with a sample size of 75 respondents who are consumers of Kopi Kenangan. The data analysis technique employs SmartPLS version 4 through outer model and inner model testing. The results show that content marketing has a positive and significant effect on purchasing decisions, while influencer marketing has a negative and significant effect on purchasing decisions. Content marketing and influencer marketing have a positive and significant effect on content creation. Content creation also has a positive and significant effect on purchasing decisions. In addition, content creation is proven to significantly mediate the effect of content marketing and influencer marketing on purchasing decisions. The findings of this study emphasize that content quality plays an important role in increasing consumer purchase intention, while the selection of influencers must be more selective to align with the brand persona.